Developing Student Motivation Through Scientific Writing Learning Guidance - Nur Intan Ode, Muhamad; Suherman, La Ode Achmad (Room of Civil Society Development, 2022)
In this community service project, tutoring will be highlighted. Tutoring is used in this activity to provide students with a range of perspectives on the knowledge they have learned as a consequence of their own experiences with their surroundings. Students contribute significantly to the development of thinking abilities through their use of language in scientific papers. The approaches used in this service activity include explanation and practice. This is because students' understanding and writing abilities are limited, making it harder for them to produce scientific articles. One aspect of student development is the development of the capacity to write scientific articles. This capability is immediately obvious in well-structured writing. The findings of this study show that students were able to write scientific papers as a consequence of this service, allowing them to grow and think creatively while finishing their studies through the production of scientific papers, and that students are proficient at writing scientific papers.